Control in grammar and pragmatics : a cross-linguistic study - Růžička, Rudolf (Linguistik aktuell, 1999)
The claim that " ... pronominals have phonological features only where they must, for some reason", is strongly supported by the occurrence of the null pronoun PRO as coined and introduced by Noam Chomsky. How reference of PRO is determined is the main subject of control theory, the subsystem of core grammar to which this study is dedicated. Chomsky has not followed up his "natural suggestion that choice of controller is determined by theta roles or other semantic properties of the verb, perhaps pragmatic conditions of some sort."But then, a great many students of control have engaged in exp.